Quality of life indicators associated with the functionality of older people in Brazilian amazon: a network analysis approach - Cleidson Colares Batista; Talita Cezareti da Silva; Elaine Cristina Costa Lopes; Renato Augusto Mariotto; Tania Maria Gomes da Silva; Aliny Lima Santos; Aline Diniz Gehren; José Roberto Andrade do Nascimento Júnior; Daniel Vicentini de Oliveira (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: The relationship between quality of life (QoL) and functionality is a critical aspect of healthy aging, reflecting the interconnectedness of physical, psychological, and cognitive health.